Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1302/0301-620x.74b1.1732267
|View full text |Cite
|
Sign up to set email alerts
|

Resorption of bone by inflammatory cells derived from the joint capsule of hip arthroplasties

Abstract: The role of inflammatory cells in aseptic loosening and failure of cementedjoint replacements is unclear. Inflammatory cells from the revisionjoint capsule offour failed hip arthroplasties were examined to determine their nature and resorptive capacity. The capsules contained numerous macrophages and abundant foreignbody macrophage polykaryons, distinguished from osteoclasts by their antigenic phenotype and lack of response to calcitonin. When cultured on cortical bone slices in vitro, both macrophages and mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(64 citation statements)
references
References 13 publications
4
58
0
2
Order By: Relevance
“…A previous in vitro study showed resorption pits on bone slices incubated with inflammatory cells exposed to particles for 4 days [3]. We performed pre-and postexperimental microCT scans in vivo to detect changes in BMD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous in vitro study showed resorption pits on bone slices incubated with inflammatory cells exposed to particles for 4 days [3]. We performed pre-and postexperimental microCT scans in vivo to detect changes in BMD.…”
Section: Methodsmentioning
confidence: 99%
“…Macrophages can resorb bone directly or differentiate into osteoclasts, the primary bone-resorbing cells, to undermine the prosthetic bed [3,33]; furthermore, the increased levels of reactive oxygen species produced during phagocytosis of wear debris will impair periprosthetic bone formation as a result of the increased cytotoxicity to osteoprogenitor cells [46]. Numerous in vivo and in vitro models have been developed to investigate the interactions among macrophages and other cells, wear debris, and osteolysis [1, 3, 8, 12, 16-20, 22, 29, 30, 33, 34, 42].…”
Section: Introductionmentioning
confidence: 99%
“…However, attributable in part to PEEK's relatively inert and hydrophobic surface, recent evidence has demonstrated that smooth PEEK can exhibit poor osseointegration [9,25] and fibrous capsule formation around the implant [23,34]. Lack of bone-implant contact can induce micromotion and inflammation that leads to fibrous layer thickening, osteolysis, and implant loosening [2,13,29,37,48]. Previous studies [1,4,15,16,18,36] have shown that surface modifications such as plasma treatments, coatings, and composites can improve PEEK implant integration, yet many suffer practical limitations such as delamination, instability, and mechanical property tradeoffs.…”
Section: Introductionmentioning
confidence: 99%
“…(2) What is the effect of pore size on the mechanical properties of PEEK-SP? (3) Do surface porosity and pore size influence the cellular response to PEEK?…”
Section: Introductionmentioning
confidence: 99%
“…This is largely because direct evidence of bone resorption by these cells has not clearly been demonstrated. However, there is now increasing evidence to show that mononuclear phagocytes derived from inflammatory and neoplastic lesions are capable of bone resorption (Athanasou et al, 1989;Athanasou et al, 1991;Athanasou et al, 1992), and that osteoclast-like cells can form directly from tissue macrophages (Udagawa et al, 1990). …”
mentioning
confidence: 99%